Identification and characterization of the causative agents of Focal Ulcerative Dermatitis in commercial laying hens - Ayala, Diana I.; Grum, Daniel S.; Evans, Nicholas P.; Russo, Kay N.; Kimminau, Emily A.; Trible, Benjamin R.; Lahoti, Manohar M.; Novak, Curtis L.; Karnezos, Theodore P. (Frontiers in Veterinary Science, 2023)
Focal Ulcerative Dermatitis (FUDS) is an emerging dermatological disease that affects cage-free laying flocks, it is characterized by the development of a lesion on the dorsum of the birds; FUDS is sporadic in nature and can result in a drop in egg production and up to 50% of cumulative mortality. A total of two cage-free flocks (flock 1: no history of FUDS; flock 2: birds affected with FUDS) from a commercial laying hen operation in the mid-west U.S. were sampled in this study. The microbial composition of skin, cloacal, cecal, and ileal samples from each bird was characterized through next generation sequencing (NGS). Results identified Staphylococcus aureus and Staphylococcus agnetis as the potential causative agents of FUDS, being the most predominant in FUDS positive birds. These results were confirmed by plating, with both staphylococci as the only pathogens isolated from lesions of FUDS positive birds. A total of 68 confirmed Staphylococcus isolates from skin and environmental samples were further analyzed by whole genome sequencing (WGS) for the presence of antimicrobial resistance (AMR) genes and virulence factors that could have contributed to the development of FUDS. Forty-four-point one-two percent of the isolates had between one and four acquired AMR genes encoding for macrolides, lincosamides, spectrogramines, and beta-lactams resistance. Six classes of virulence factors associated with adherence, enzyme, immune evasion, secretion system, toxin, and iron uptake were identified. The antimicrobial effect of 4 proprietary Bacillus Direct Fed Microbial (DFM) combinations was evaluated against the Staphylococcus aureus and Staphylococcus agnetis isolates, by agar well-diffusion (AWD) assay and competitive exclusion (CE) on broth culture. Through this antimicrobial screening, a particular two-strain combination of Bacillus pumilus was identified as the most effective inhibitor of both staphylococci. A customized Bacillus pumilus product is being used at different farms with history of FUDS resulting in the successful inhibition of both Staphylococcus aureus and Staphylococcus agnetis, decreasing FUDS mortalities, and improving harvestable eggs.